2008
DOI: 10.1016/j.bbrc.2008.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine attenuates inflammation and NF-κB activation via Cullin-1 deneddylation

Abstract: Glutamine (GLN) can inhibit NF-kB activation and cytokine expression following sepsis. NF-kB activation and inflammatory cytokine expression, depend on neddylation of Cullin-1 (Cul-1) to proceed. Our aim was to evaluate whether GLN inhibits Cul-1 neddylation, and further determine if GLN-mediated Cul-1 deneddylation attenuates NF-kB activation and subsequent cytokine expression following experimental sepsis in the mouse. Sepsis induced via cecal-liagtion and puncture (CLP) led to a significant increase in lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
2
36
0
1
Order By: Relevance
“…Such a critical role for NF-B in mediating the anti-inflammatory effects of glutamine has also been reported for TNBS colitis in rats (23). Another report indicated that glutamine treatment leads to Cullin-1 deneddylation and in turn NF-B inhibition in mice (40). In contrast to the well-established role of NF-B in other forms of colitis (39), its role in GvHD is not completely clear.…”
Section: Discussionmentioning
confidence: 90%
“…Such a critical role for NF-B in mediating the anti-inflammatory effects of glutamine has also been reported for TNBS colitis in rats (23). Another report indicated that glutamine treatment leads to Cullin-1 deneddylation and in turn NF-B inhibition in mice (40). In contrast to the well-established role of NF-B in other forms of colitis (39), its role in GvHD is not completely clear.…”
Section: Discussionmentioning
confidence: 90%
“…Glutamine and leucine are two important amino acids that dictate metabolism and signaling in proliferating cells and both have been demonstrated to have anti-inflammatory properties (Singleton and Wischmeyer, 2008; Sengupta et al, 2010). The requirement for these amino acids in starvation-induced PI3K phosphorylation was next tested by stimulating WT mEFs with HBSS or HBSS supplemented with L-glutamine, L-leucine, a mixture of non-essential amino acids (NEAA), or serum.…”
Section: Resultsmentioning
confidence: 99%
“…In our study the addition of 2 mM glutamine to incubation media appeared to promote the release of pro-inflammatory mediators [43], which could be reflective of experimental conditions, levels of extracellular HSP70 release or glutamine levels within the in vitro model. The cellular response to infection is a complex process co-ordinated by a wide range of intra-and extracellular mediators.…”
Section: LV Marino Et Al / Clinical Nutrition Xxx (2014) 1e7mentioning
confidence: 65%